The Management of Building Industry Knowledge - Torrech Jr., José Rolando (Artes: Architecture, Technology and Sustainability, 2023)
Due to the information-centric nature of the architecture and construction sector, knowledge management has been implemented. However, there are several obstacles to implementing knowledge management (KM) in the construction industry because of the prevalence of outdated methods. Therefore, methods must be developed to address inefficiency, boost KM, and combine technological advancements with creative thinking. Such methods are critical to improving KM’s efficiency and laying the groundwork for future success. With the use of cutting-edge technology and creative thinking, this research analyzed the most effective models and procedures for knowledge management in the building and construction sectors. The study employed a descriptive research design and a qualitative technique. Content analysis was used to decipher responses to open-ended questionnaires. The findings call for the implementation of both organic and mechanized approaches, as well as software systems, building information management (BIM), digitization, and the blockchain. Due to the ever-changing nature of knowledge management, it is essential for companies operating in this industry to continually strengthen their internal resources and adapt their approach.